Legal Compliance In Realizing The Attitude Of Defending The State For College Student Upn Veteran East Java - Indawati, Yana; Yulianingsih, Wiwin (VJJ, 2020)
This Research aim to find the connection between legal awareness UPN “Veteran” Jawa Timur College student with state defense attitude. Legal awareness is awareness or values contained in man about the existing law or about laws that are expected to exist. Actually, what is emphasized is the values regarding the function of the law and not a legal assessment of it concrete events in the community concerned. Legal awareness is very important in measuring the level of state defense attitudes. There are several indicators of the problem of legal awareness, namely Knowledge of legal regulations (law awareness); Knowledge of the contents of legal regulations (law acquaintance); Attitude towards legal regulations (legal attitude); Legal behavior patterns (legal behaviour). All indicators are related to campus regulations. Legal awareness, especially regarding student compliance in obeying the rules set by the campus. the higher the level of violation of campus discipline, the greater the reduction of student defending attitudes. The method used in this study begins with identification from various literatures related to the legal awareness culture of students towards university regulations and policies in terms of the problems that occur and the challenges that must be faced by the university. Then arranged in such a way as to bring up the right problem formulation which later can be comprehensively reviewed through field studies and direct observation, especially related to the problems taken in this study, namely the application of campus regulations to realize the attitude of defending the State in students. The research results in this study are expected to be able to contribute to the university and the development of students who are expected to have a spirit and attitude to defend the country.